Pengaruh Latihan Passing Bawah melalui Media Dinding pada Ektrakulikuler Bola Voli SMA Negeri 1 Ayah Kabupaten Kebumen - Puput Widodo; Aldy Kurniawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The results of observations at SMA Negeri 1 Ayah, Kebumen Regency showed that students had difficulty in mastering the technique of passing under the ball in volleyball. This study aims to measure the effect of training in passing under the ball through the wall media on the passing ability of under the ball students participating in extracurricular activities. This study used a "one group pretest-posttest" design by measuring passing skills before and after treatment in different groups, which is suitable for identifying changes in skills. The population in this study were 33 students who were active in the extracurricular volleyball team of SMA Negeri 1 Ayah who met the research criteria. The selection of samples in this study used a purposive sampling technique. The sample used by the researcher in this study consisted of 10 students. Based on the analysis of the research data, the experimental research group had an impact on changes in the influence on the results of passing under the ball in volleyball. On average, the percentage of the experimental research group using treatment in the form of wall media training had a greater impact. So it can be concluded that training using wall media with the target wall has an effect on passing under